58‐2: Revealing the Excited‐state Dynamics of Thermally Activated Delayed Flourescence Molecules by using Transient Absorption Spectrospy. Issue 1 (May 2016) - Hosokai, Takuya; Matsuzaki, Hiroyuki; Furube, Akihiro; Tokumaru, Katsumi; Tsutsui, Tetsuo; Nakanotani, Hajime; Yahiro, Masayuki; Adachi, Chihaya
Abstract : Excited state dynamics is a central issue in discussing the origin of the high efficiency of thermally activated delayed fluorescence (TADF) molecules. Here we will present experimentally a complexity of the excited state dynamics of the extremely high efficient TADF molecules, 4CzIPN. By means of pump‐probe transient absorption spectroscopy, we will show the sign of intramolecular charge delocalization formed in the excited state. This specific excited state originates from the intramolecular charge resonance within carbazole moieties, which occurs through the dimerization of the moieties. On the other hand, the counter molecules of 4CzIPN, i.e. 2CzPN, forms only a localized excited state. The role of charge delocalized state for TADF efficiency will be discussed.